A family-based multimedia intervention to enhance the uptake of colorectal cancer screening among older South Asian adults in Hong Kong: a study protocol for a cluster randomized controlled trial - Winnie K. W. So; Bernard M. H. Law; Kai Chow Choi; Dorothy N. S. Chan; Carmen W. H. Chan (BMC, 2019)
Abstract Background Colorectal cancer (CRC) screening, such as fecal occult blood test (FOBT), is an effective way to prevent CRC, one of the most common cancers worldwide. However, studies found that South Asian ethnic minorities tend not to utilize CRC screening, whose importance on CRC prevention shall be educated among those from ethnic minorities, especially older adults. The purpose of this study is to develop and implement a family-based, multimedia intervention to augment the knowledge of CRC prevention among older South Asian adults in Hong Kong and enhance their motivation for undergoing FOBT. The acceptability and effectiveness of the intervention will be assessed using the Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) framework. Methods A cluster randomized controlled trial will be carried out. Three hundred and twenty South Asian dyads, comprising an older adult aged between 50 and 75 and a younger family member aged between 18 and 49, will be recruited in ten districts in Hong Kong through community organizations that provide support services for South Asians in local communities. Dyads will be randomly allocated to either the intervention or wait-list control group. Intervention dyads will receive intervention, whose contents are based on the health belief model, via multiple forms of media including PowerPoint presentation, video clip and health information booklet. Control dyads will receive intervention after post-intervention data are collected. For dyads in both groups, an appointment with a family doctor will be arranged for those willing to undergo FOBT. Outcomes will be assessed at baseline and post-intervention. Data will be analysed using the Generalised Linear Models Procedure in an intention-to-treat manner. Discussion Findings of this study will provide evidence of the benefits of utilizing multimedia and family-based approaches in intervention development to enhance the effectiveness of health promotion interventions for ethnic minorities. Further, the findings would provide reference to the potential incorporation of the intervention in the existing support services for South Asian ethnic minorities in local communities. Trial registration This trial is registered at the ISRCTN Registry (ISRCTN72829325) on 19th July 2018.